Utilization of Yeasts in Promoting Plant Growth in Acidic Soil – A Review - Rawichandran, Darshini; Kasim, Susilawati; Kee Zuan, Ali Tan; Effendi, Mohd Izuan; Raguraj, Sriharan (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
The ecosystem's biodiversity and soil microorganisms are impacted by the increasing use of synthetic fertilizers and pesticides, which causes soil acidity and limits the sustainability of agricultural output. The majority of microbial functions in acidic soil are inhibited because of decreasing nutrient cycling and organic matter decomposition as well as diminishing bacterial and fungal growth and reproduction. In light of these growing concerns, the use of microorganisms as bio fertilizers is a recommended as alternative agricultural practice. Recent times have brought about a change in the paucity of study on yeasts and their ability to safely boost plant growth. Numerous works on bacteria have been made available. The primary objective of the study is to highlight the widespread application of yeasts in sustainable agricultural practices to promote plant growth in acidic soils. All of the advantages that yeasts provide may contribute to the growth of plants. Therefore, a thorough investigation into yeasts may be fruitful and offer a sustainable means of boosting agricultural yields that are necessary in acidic soil.